Management of Nonhealable and Maintenance Wounds: A Systematic Integrative Review and Referral Pathway. (January 2021) - Boersema, Geertien C.; Smart, Hiske; Giaquinto-Cilliers, Maria G. C.; Mulder, Magda; Weir, Gregory R.; Bruwer, Febe A.; Idensohn, Patricia J.; Sander, Johanna E.; Stavast, Anita; Swart, Mariette; Thiart, Susan; Van der Merwe, Zhavandre
Abstract : GENERAL PURPOSE: To synthesize the evidence regarding nonhealable and maintenance wound management and propose an interprofessional referral pathway for wound management. TARGET AUDIENCE: This continuing education activity is intended for physicians, physician assistants, nurse practitioners, and nurses with an interest in skin and wound care. LEARNING OBJECTIVES: After participating in this continuing professional development activity, the participant will apply knowledge gained to: 1. Identify the ideas from the authors' systematic review that could prove useful in understanding nonhealable and maintenance wound management. 2. Select evidence-based management strategies for nonhealable and maintenance wound management. ABSTRACT: OBJECTIVE This systematic integrative review aims to identify, appraise, analyze, and synthesize evidence regarding nonhealable and maintenance wound management to guide clinical practice. An interprofessional referral pathway for wound management is proposed. DATA SOURCES: An electronic search of Scopus, Web of Science, PubMed, Academic Search Ultimate, Africa-Wide Information, Cumulative Index of Nursing and Allied Health Literature database with Full Text, Health Source: Consumer Edition, Health Source: Nursing/Academic Edition, and MEDLINE was conducted for publications from 2011 to 2019. Search terms included (nonhealable/nonhealing, chronic, stalled, recurring, delayed healing, hard-to-heal) and wound types most associated with nonhealable or maintenance wounds. Published studies were hand searched by the authors. STUDY SELECTION: Studies were appraised using two quality appraisal tools. Thirteen reviews, six best-practice guidelines, three consensus studies, and six original nonexperimental studies were selected. DATA EXTRACTION: Data were extracted using a coding framework including treatment of underlying causes, patient-centered concerns, local wound care, alternative outcomes, health dialogue needs, challenges within resource restricted contexts, and prevention. DATA SYNTHESIS: Data were clustered by five wound types and local wound bed factors; further, commonalities were identified and reported as themes and subthemes. CONCLUSIONS: Strong evidence on the clinical management of nonhealable wounds is limited. Few studies describe outcomes specific to maintenance care. Patient-centered care, timely intervention by skilled healthcare providers, and involvement of the interprofessional team emerged as the central themes of effective management of maintenance and nonhealable wounds. Abstract : Supplemental digital content is available in the text.